The Impact of Conical and Nonconical Abutments on Bacterial Infiltration at the Implant-Abutment Interface - Guerra, Elen [UNESP]; Pereira, Cristiane [UNESP]; Faria, Renata [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP]; Bottino, Marco Antonio [UNESP]; Melo, Renata Marques de [UNESP] (Quintessence Publishing Co Inc, 2016)
This study evaluated the in vitro bacterial microleakage at the implant-abutment interface of three prosthetic connections: external (EH) and internal hexagon (IH) and taper connection (TC: solid [ST], taper with internal hexagon [IT], and short taper [OT]). Escherichia coli (E coli) and Streptococcus sanguinis (S sanguinus) were inoculated in the apical portion of the abutment screw, which was immersed in sterile brain-heart infusion broth for 14 days. There were no differences between the percentages of bacterial iniltration for IH (9.09%), ST (21.74%), IT (22.73%), and OT (11.11%). EH did not present viable bacteria. There were no signiicant differences in the counts of connections inoculated and not infiltrated by E coli or S sanguinis nor in those infiltrated by both bacteria (one-way analysis of variance, P < .05). Except for EH, all implant designs and abutments showed bacteria that were capable of surviving and causing infiltration.